Problem and Prospects of Nepali Historiography - Bhandari, Arjun Bahadur (Journal of Interdisciplinary Studies, 2021)
The art of writing history, developed from the 5th century BC with an account of the personal events and epics of kings, emperors, war events. Now the historian has begun the scientific approach on history writing based on the collection, analysis and refinement of facts by scientific method. Reflection of Political change around the world has been seen in history writing. After the democratization of the world it should be more transparent and people oriented. In opposite to democratic value (historiography should be more transparent, scientifically credible, people based and reliable), spontaneity have been introduced in historiography. Historiography could not remain untouched by the effects of change around the world and Nepali historiography didn’t become an exception in this context. It is found that the work of writing the history of Nepal started from foreign scholars. Since the military officers and foreign diplomats who came to Nepal after the Sugauli Treaty (1816 A.D.) were the beginners of writing the history of Nepal. Some of the contexts of the history written by those foreigners seem to be more controversial and subjective than factual. The English and European historians who contributed to the writing of the history of Nepal, they didn’t understand the essence of scientific historiography. Also, their attitude towards Nepal and Nepalis was not respectable. The history written by such officials and the context of rewritten history giving details of the same history has not become credible in today’s world of science. More recently, social issues such as ethnicity, regionalism has been distorted and misinterpreted and social hatred has been spread through history. History written today with subjectivity, passed on to future generations, it will be against the spirit and essence of scientific historiography. This article is based on qualitative research and seeks to discuss the challenges faced by historian on contemporary Nepali historiography. In-depth interview and library research approaches are being employed to collect the data. This is a descriptive study limited to historical research. This article also emphasizes the Nepali historian to accept the challenge seen in writing Nepali history and pass on the truth, facts and scientific history to the future generation. Many Nepali scholars have contributed in Nepali historiography but they are not free from the traditional perspective thus it is the time to write Subaltern history to explore the real Nepali historiography to the writing of factual Nepali history.